Mathematical Information Retrieval (MIR) from scanned PDF and MathML conversion - Nazemi, Azadeh; Murray, Iain; McMeekin, David (Information Processing Society of Japan, 2014)
This paper describes part of an ongoing comprehensive research project that is aimed at generating a MathML format from images of mathematical expressions that have been extracted from scanned PDF documents. A MathML representation of a scanned PDF document reduces the document's storage size and encodes the mathematical notation and meaning. The MathML representation then becomes suitable for vocalization and accessible through the use of assistive technologies. In order to achieve an accurate layout analysis of a scanned PDF document, all textual and non-textual components must be recognised, identified and tagged. These components may be test or mathematical expressions and graphics in the form of images, figures, tables and/or diagrams. Mathematical expressions are one of the most significant components within scanned scientific and engineering PDF documents and need to be machine readable for use with assistive technologies. This research is a work in progress and includes multiple different modules: detecting and extracting mathematical expressions, recursive primitive component extraction, non-alphanumerical symbols recognition, structural semantic analysis and merging primitive components to generate the MathML of the scanned PDF document. An optional module converts MathML to audio format using a Text to Speech engine (TTS) to make the document accessible for vision-impaired users.